Strategi Kewirausahaan Melalui Pemasaran Sempol Ayam Pada Simpang Kandis Kota Bengkulu - Rafles, Fadhlu Rohman Dian (Jurnal Kewirausahaan dan Bisnis, 2024)
Marketing management is a measurable action aimed at knowing the company's products to the wider community. marketing tactics are very important in doing business, so that businesses are able to market products to be synchronized with sales targets, marketing strategies carried out will result in what will happen aporisma, namely marketing products in accordance with processed production and desired profits. The research was conducted at the sempol ayam sales place in Simpang Empat, Simpang Kandis, Kampung Melayu District, Kelurahan Kandang. This article also uses a qualitative method using a literature study approach. The data used is data obtained through interviews conducted exclusively.